To Determine the Common Causes Leading to Pancytopenia in Patients Presenting to Tertiary Care Hospital, Lahore - Khadija Muneer, Mougheesa Baig, Bushra Asif Sheikh, Muhammad Awais Abid, Hafsa Farooq, Asma Kamal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: New-onset pancytopenia can be caused by a wide variety of etiologies, leading to an array of prolonged and invasive investigations. Knowing the important differentials can help in targeted screening and early diagnosis. The reported frequency of common causes of pancytopenia varies among existing studies due to population and geographic differences in dietary habits and environmental and genetic factors, thus necessitating the present study. The goal is to determine the frequency of the leading causes of pancytopenia in patients presenting to the hospital. Subjects and methods: This study is a cross sectional study involving 140 patients of both genders aged between 12 to 80 years presenting with pancytopenia to Sir Ganga Ram hospitals, Lahore. These patients underwent detailed clinical and lab evaluation to identify the underlying cause of pancytopenia e.g. aplastic anemia, megaloblastic anemia, hypersplenism and acute leukemia. The etiological spectrum of pancytopenia was stratified by various subgroups of patients based on age and gender. A written informed consent was taken from each patient. Results: The mean age of the patients was 47.2±19.9 years. There were 90 (64.3%) male and 50 (35.7%) female patients in the study group with a male to female ratio of 1.8:1. Among the underlying causes of pancytopenia, aplastic anemia was most frequent and was observed in 54 (38.6%) patients followed by megaloblastic anemia (n=39, 27.9%), hypersplenism (n=24, 17.1%) and acute leukemia (n=23, 16.4%). Upon stratification, no statistically significant difference was observed in the frequency of various underlying causes of pancytopenia across various subgroups of patients based upon age and gender. Conclusion: In the present study, aplastic anemia and megaloblastic anemia were found as the most frequent cause underlying pancytopenia regardless of patient’s age and gender. This advocates their consideration as important differentials in the diagnostic evaluation of patients presenting with pancytopenia in future medical practice so that timely identification and management may improve the outcome of such cases.